Pendidikan Karakter Anak Usia Dini Berbasis Aqidah Akhlak - Unik Hanifah Salsabila; Muhamad Syaifudin Zuhri; Muhamad Arya Rahmandhani; Abdurrahman Wahid Alimi (UIN Mataram, 2020)
Character development must start early. Developing and shaping characters cannot bedone instantly. The primary character education comes from the family and theenvironment before school. The role of educators to direct and guide students is the keypoint. Character education based on aqidah ahlak (moral faith) is also very wellimplemented because Islam has taught what needs to be done to shape a person'scharacter. Islam has provided a lot of teachings in the Al-Qur'an and Hadith regarding howhumans learn and obtain good morals and behavior. This article aims to explain charactereducation for early childhood based on moral faith. By conducting qualitative researchmethod, this article is created by collecting data from books, related journals, ebooks, andpdf. This article contains the concept of moral faith education, the purpose of moral faitheducation, and the scope of moral faith. The concept and purpose of character educationbased on moral faith is the formation of children character. This character is formed in linewith what has been taught in Islam in which the goal is to create children possessing noblemorals.